Recent evolution of the tidal prisms at the inlets of the western sector of the Ria Formosa, south coast of Portugal - Jacob, J. (2020)
The Ria Formosa is a coastal lagoon comprising six tidal inlets. The western sector encompassing three inlets, Ancao, Faro-Olhao and Armona is the most important one since it represents approximately 90% of the total tidal prism. The Ancao inlet is characterized by a cyclic eastward migration pattern, but until now the knowledge of the real impact of its dynamics in the last 20 years in terms of tidal prisms and interconnectivity between these three inlets is scarce. This work presents the most exhaustive data set acquired so far, comprising 25 field surveys led in the period 2004-2013 on the western sector of Ria Formosa. This provides a long-term analysis of the recent temporal evolution of the tidal prisms from the three inlets during a single migration cycle (18 years) of the Ancao inlet. It determines the relative contribution of the three inlets to the total prism of the western sector of Ria Formosa before the last artificial opening of the Ancao inlet. Results show that at Ancao inlet the tidal prism decreased in spring tide mainly due to its eastward migration. The other natural inlet, Armona inlet, depict a progressive narrowing responsible for the decrease of the tidal prism in neap tide while during the same tidal phase, at the Faro-Olhao inlet, the most important one in terms of exchanges, the tidal prism increased. Those alterations at the three inlets could be related to morphodynamic changes and morphological evolution and confirmed the strong interconnectivity between them to compensate the variations of their relative contributions to the total prism. The tidal prisms errors were low for all cases (< 10%) and confirm that, globally, there was an increase of the prisms with time.